2018
DOI: 10.26656/fr.2017.2(6).107
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzed water as a green cleaner: chemical and physical characterization at different electrolysing parameters

Abstract: The aims of this study were to develop electrolysed technique and evaluate the characteristics and performance of electrolysed water that will be applied as a cleaning medium in the food industry. Acidic electrolyzed water (AcEW) and neutral electrolyzed water (NEW) have been reported to have a strong bactericidal effect on various types of foodborne pathogens for many types of food products and food equipment surfaces. While alkaline electrolyzed water (AlEW) is a potential cleaning medium for alkaline wash. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Current efficiency is, according to Faraday's law, the ratio of the actual mass of a substance liberated from an electrolyte by the current's passage to the theoretical mass liberated [12]. Equations ( 1) to (3) were used to calculate the theoretical total chlorine [12]. The mass of chlorine produced from the electrolysis experiments was calculated using Equation (4).…”
Section: Electrolysis Efficiency For Chlorine Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current efficiency is, according to Faraday's law, the ratio of the actual mass of a substance liberated from an electrolyte by the current's passage to the theoretical mass liberated [12]. Equations ( 1) to (3) were used to calculate the theoretical total chlorine [12]. The mass of chlorine produced from the electrolysis experiments was calculated using Equation (4).…”
Section: Electrolysis Efficiency For Chlorine Productionmentioning
confidence: 99%
“…Hsu et al [36] concluded that the electrical conductivity of an electrode is mainly responsible for the production of chlorine. However, studies conducted by Khalid et al [12] revealed that a titanium-silver pairing with higher electrical conductivity (σ of silver = 6.3 × 10 7 S/m) produced a lower chlorine content compared with a titanium-stainless steel pairing (σ of stainless steel= 1.45 × 10 6 S/m) (0.17 and 0.5 mg Cl 2 /L, respectively). The quantity of chlorine generated is significantly low in the study conducted by Khalid et al [12] as the lab-scale electrolyzing unit has a low current efficiency.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations